Effect of faulting on diagenetic processes in the silicate-sulfate-carbonate system: A case study from the Bonan Sag of Jiyang Depression, Bohai Bay Basin. (January 2023) - Ma, Pengjie; Lin, Chengyan; Dong, Chunmei; Ren, Lihua; Jahren, Jens; Hellevang, Helge; Lin, Jianli
Abstract: Many extraordinary cements, including mosaic dolomite, poikilitic celestine–barite, anhydrite and chemically zoned saddle-formed dolomite–ankerite, were observed in a reservoir sandstone unit underlying an evaporite sequence in the northern Bonan Sag, which is a saline lacustrine rift basin in the Jiyang Depression of Bohai Bay Basin, China. A suite of petrologic and chemical methods, including optical observation with cathode luminescence, fluid inclusion with laser Raman spectroscopy, X-ray fluorescence, and stable isotopes of carbon, oxygen and sulfur, were carried out. The results suggest that these extraordinary cements are mainly distributed near a fault zone and related to episodes of faulting events. Fault rupturing at shallow burial depths resulted in the dislocation of the evaporites and sandstones and made it possible for an influx of alkaline fluid from evaporites into the fault zone, where mosaic dolomite precipitated, and near fault reservoir units, such as where celestine–barite precipitated. Within the 'oil window', the reactivated normal faults, which induced a pressure drop in the reservoir unit, may have resulted in gas influx (e.g., CO2 and H2 S) and hydrocarbon charging, enhancing K-feldspar dissolution and cementation of assemblages of quartz, albite and illite. The cyclic fault rupturing and sealing in this setting probably resulted in repeated 'openness' of the diagenetic system, chemical perturbation of the pore fluids (e.g., pH dropping and returning), and cyclic dissolution–regrowth within the silicate–sulfate–carbonate diagenetic system. This study may highlight the awareness of diagenetic complexity in fault zones and shed light on reservoir evaluation in rift settings. Highlights: The fault-controlled authigenic cements of mosaic dolomite and poikilitic celestine–barite were observed in near-fault reservoir. K-feldspar dissolution and cementation of assemblages of quartz, albite and illite are more developed in the vicinity of faults. The curved dolomite–ankerite and associated blocky pyrite are suggested as the byproducts of thermochemical sulfate reduction. Fault events are significant for cyclic dissolution-precipitation processes in the silicate-sulfate-carbonate system.